2000
DOI: 10.1680/macr.2000.52.4.251
|View full text |Cite
|
Sign up to set email alerts
|

Gas permeability of unsaturated cement-based materials: application of a multi-scale network model

Abstract: A multi-scale network model based on the percolation theory and using a renormalization method was applied to describe the porous space of cement-based materials and to determine their gas transport properties. Gas permeability was measured on hardened cement pastes prepared with French OPC (CEM I) and BFS±PFA (CEM V) cements currently used in the nuclear waste industry. These experiments were carried out to study the influence of the degree of water saturation and of the microstructure on materials gas transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…The measured value of oxygen permeability of cementitious materials not only depended strongly on its degree of saturation but varied with the applied pressure. Galle and Daian [4] carried out gas permeability tests on unsaturated hardened cement pastes prepared with CEM I and CEM V cement with water-to-cement (w/c) ratios of 0.3, 0.4 and 0.5 and reported that the gas permeability of cement pastes was significantly influenced by degree of water saturation and microstructural characterisations of the specimens, such as porosity and pore size distribution. The relationship between gas permeability and degree of water saturation followed a nonlinear regression.…”
Section: Introductionmentioning
confidence: 99%
“…The measured value of oxygen permeability of cementitious materials not only depended strongly on its degree of saturation but varied with the applied pressure. Galle and Daian [4] carried out gas permeability tests on unsaturated hardened cement pastes prepared with CEM I and CEM V cement with water-to-cement (w/c) ratios of 0.3, 0.4 and 0.5 and reported that the gas permeability of cement pastes was significantly influenced by degree of water saturation and microstructural characterisations of the specimens, such as porosity and pore size distribution. The relationship between gas permeability and degree of water saturation followed a nonlinear regression.…”
Section: Introductionmentioning
confidence: 99%
“…These observations may be due to the moisture distribution. As indicated previously, water absorption is able to remove the effect of capillary suction, but only the top surface layer is saturated by this treatment (13,28). If the water flow remained in the top surface region during the 1 bar [14.5 psi] test, where capillary effect was insignificant, a low flow rate was generally observed.…”
Section: Assessment Of Reliability Of Two Pressure Head Techniquementioning
confidence: 65%
“…It is clear that in all cases (C1-C4), the flow rates of AC are much higher than those of MC and SC. This links in the fact that the three curing regimes resulted in different permeation properties and initial moisture contents at near surface concrete (28,29). MC refers to the moisture cured concrete, under which condition additional moisture was present in the concrete and no significant drying occurred from the surface in the whole curing period.…”
Section: Determination Of Steady-state Flow Rate Under Two Pressure Hmentioning
confidence: 99%
“…Tests are generally conducted in a steady state on unsaturated soils (Eischens and Swanson 1996;Samingam et al 2003), rocks (Cosse 1996), geosynthetic clay liners (Didier et al 2000;Shan and Yao 2000;Bouazza and Vangpaisal 2003;Vangpaisal and Bouazza 2004), or cement-based materials (Gallé and Daian 2000;Loosveldt et al 2002). Results show that when the water content increases, corresponding to a lower volume available in the material for gas migration, measurement becomes more and more difficult, leading to relative uncertainties of up to 100% when the water content is over 100% in geosynthetic clay liners (Shan and Yao 2000;Bouazza and Vangpaisal 2003).…”
Section: Experimental Aspect and Different Testsmentioning
confidence: 99%
“…Results show that when the water content increases, corresponding to a lower volume available in the material for gas migration, measurement becomes more and more difficult, leading to relative uncertainties of up to 100% when the water content is over 100% in geosynthetic clay liners (Shan and Yao 2000;Bouazza and Vangpaisal 2003). Gallé and Daian (2000) obtain an important dispersion of permeability values (four orders of magnitude) at 90% of saturation in cement-based materials.…”
Section: Experimental Aspect and Different Testsmentioning
confidence: 99%